Hollow man 2 - Faeh, Claudio; Facinelli, Peter, 1973-; Regan, Laura; McIlwraith, David; Slater, Christian; McDonald, William; Wunstorf, Peter; Trumpp, Marcus; Sony Pictures Home Entertainment (Firm) (Culver City, Calif. : Sony Pictures Home Entertainment, 2006)
A Seattle detective and a biologist find themselves the targets of murder from an invisible assassin gone rogue. Other targets for assassination are the government forces who caused him to become invisible.
Based on the characters created by Garry Scott Thompson and Andrew W. Marlowe.
Special features: "Inside 'Hollow man 2'" featurette; Visual effects featurette; Storyboard gallery; Storyboard-to-scene featurette.
Director of photography, Peter Wunstorf ; editor, Nathan Easterling ; music, Marcus Trumpp ; costume designer, Maria Livingstone ; production designer, Brentan Harron ; visual effects supervisor, Ben Grossman.
Peter Facinelli, Laura Regan, David McIlwraith, Christian Slater, William McDonald, Sarah Deakins, Jessica Harmon.
MPAA rating: R; for violence, some sexuality/nudity and language.
DVD, region 1, widescreen presentation; Dolby Digital.
Keywords: Assassins -- Drama; Detectives -- Washington (State) -- Seattle -- Drama; Biologists -- Washington (State) -- Seattle -- Drama; Feature films; Thrillers (Motion pictures); Thrillers (Television programs); Action and adventure films; Science fiction films; Horror films; Video recordings for the hearing impaired